EFEK BUDAYA MERANTAU DAN MATRILINEAL SUKU MINANGKABAU DALAM KOMUNIKASI DALAM KELUARGA DI DAERAH PERANTAUAN - muhammad ihsan zaky (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2021)
Abstract With the modern era, culture is now often left behind, with the excuse that it has been left behind. Especially in the souls of young people who tend to follow the trend. Building a feeling of cultural love can be done by showing an identity and privilege. There are many cultures and customs that exist in Indonesia, one of which is the custom of Kabau. There are two cultures that are very prominent in the Minang custom, namely wandering and matrilineal culture. These two cultures really affect Minang children, especially in the family and overseas. The formulation of the problem is how does culture affect the character of children? The purpose of this study is to determine the influence of culture in educating children in the family sphere. The research method used is a qualitative method. In this study, I used a descriptive qualitative research method. This method is applied by describing the results of my interview with the Minangkabau tribe couple who migrate and live overseas. Keywords: Komunikasi lintas budaya, Adat Minangkabau, Matrilineal,Rantau